The Influence of the REMAP-GI Learning Model (Reading, Concept Map-Group Investigation) on the Activities and Learning Outcomes of Eleventh Grade Students on Cell and Bioprocess Material at SMA Negeri 10 Gowa - Andi Nurmiati; Muh. Khalifah Mustami; Ainul Uyuni Taufiq (UNIVERSITAS KHAIRUN, 2026)
This study aims to determine the implementation of the REMAP-GI learning model in class XI of SMAN 10 Gowa, determine the learning activities of class XI students at SMAN 10 Gowa who are taught using the REMAP-GI learning model;determine the learning outcomes of class XI students at SMAN 10 Gowa who are taught using the REMAP-GI model; to determine the effect of the REMAP-GI learning model on the learning activities of students in class XI at SMAN 10 Gowa; determine the effect of the REMAP-GI learning model on the learning outcomes of students in class XI at SMAN 10 Gowa. The method used was a quasi-experiment with a nonequivalent control group design. The results showed that the average learning activity of students in the control class was 80.50 (active category), while that of the experimental class was 83.00 (very active category). The average learning outcome of the control class was 79.50 (high category), and that of the experimental class was 85.83 (very high category).